2016
DOI: 10.31258/dli.3.2.p.64-76
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Kepentingan dan Interaksi Sosial Pedesaan: Studi Implikasi Alih Fungsi Lahan

Abstract: Land-use changes or land conversion issues not only poses a threat of ecological or environmental, but also trigger a variety of dynamics and complexity of social relations in it. West Cilebut Villages has been the target of investors and developers of housing since the 1990s, and now the West Cilebut Villages has changed from an area full of green “romantic” village, into the region filled with concrete. Therefore, this study was conducted to answer fundamental issues related to the issue of land conversion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies that are relevant to this study are: (1) research on social changes in the West Cilebut village community after the conversion of plantation land into housing [16]; (2) research on individual and general interests in the novel Anak Rantau by Ahmad Fuadi based on critical psychology [17]; (3) research that investigates cases of social change in terms of the forms, causes, and impacts experienced by the characters in the novel Pencari Harta Karun and Five On a Hike Together based on social intertextuality [18]; (4) research that examines the social behavior of the main character based on the interpersonal theory approach of William C. Schultz in the novel Confession Pariyem [19]; (5) research that examines aspects of literary psychology in the novel Sebelas Patriot by Andrea Hirata [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that are relevant to this study are: (1) research on social changes in the West Cilebut village community after the conversion of plantation land into housing [16]; (2) research on individual and general interests in the novel Anak Rantau by Ahmad Fuadi based on critical psychology [17]; (3) research that investigates cases of social change in terms of the forms, causes, and impacts experienced by the characters in the novel Pencari Harta Karun and Five On a Hike Together based on social intertextuality [18]; (4) research that examines the social behavior of the main character based on the interpersonal theory approach of William C. Schultz in the novel Confession Pariyem [19]; (5) research that examines aspects of literary psychology in the novel Sebelas Patriot by Andrea Hirata [20].…”
Section: Introductionmentioning
confidence: 99%
“…Judging from the exposure of previous studies, researchers found similarities and differences with this study. The similarities lie in the focus of social change as human actions as social beings and the same object of study in the fifth study, while the general difference lies in topics such as the approach of social change and social interaction in the influence of land conversion on the West Cilebut village community [16]; an individual psychology approach in analysing individual interests in the object of study [17]; the intertextuality theory approach in analysing the social aspects of the novel [18]; aspects of social behaviour with a different perspective, namely William C. Schulz [19]; the psychological aspects of the same object, namely the novel Sebelas Patriot [20]. In this study, researchers want to continue researching aspects of human social change that focus on individual interests experienced by the main character in Andrea Hirata's novel Sebelas Patriot.…”
Section: Introductionmentioning
confidence: 99%